Character Strengths are Prominent as Mate Preferences of Turkish Students - White, Elizabeth Michelle; Pearce, Amy R.; Khramtsova, Irina (Journal of International Students, 2011)
This study addressed the traits and characteristics that Turkish students deem most important in a long-term romantic partner. We collected quantitative and qualitative data on characteristics desired in romantic partners from students attending Bahçeşehir Üniversitesi in Istanbul, Turkey. Like our previous cross-cultural studies conducted in Japan, Russia and the United States, results supported dependability and love as the most important traits. Overall, positive internal attributes were rated as highly important and we recommend the traits associated with the positive psychology movement be more fully considered in future studies on mate preferences.